P-715 (In)fertility perceptions in a cohort of 1569 women. (30th June 2022) - Trinchant, R; Cruz, M; Mugica, A; Colomé, C; Requena, A
Abstract: Study question: Which are the perceptions and knowledge regarding female fertility and infertility of Spanish women? Summary answer: Infertility carries a social stigma that prevents women from sufficient knowledge or professional aid to take their reproductive choices adequately. What is known already: Infertility is a pathology that remains on an invisible plane for society. It is estimated that up to a third of all IVF cycles performed due to low ovarian reserve would be avoidable if women had received sufficient information at the right time. The factors that mainly contribute to this phenomenon are the marked social stigma that it entails, the lack of knowledge regarding tools, possibilities and real expectations in fertility and the low socio-sanitary involvement regarding tasks and campaigns to increase social awareness in this specific field. Study design, size, duration: This is a cross-sectional study carried out using a population-based survey to identify different attitudes, knowledge and opinions regarding fertility and infertility. The survey was made public on April 30, 2019 and closed on May 10, 2019. Participants/materials, setting, methods: A total of 1569 Spanish women answered all the questions included in the survey. No response or subject participation was excluded from the study. The platform used to create the questionnaire was Google Forms, which anonymizes the responses automatically. Data processing was performed using RStudio, an integrated development for R scripting. Main results and the role of chance: Up to 1231 women had not had children at the time of the survey and 46% (566) of these cohort were either worried or very concerned about not being able to conceive naturally in the future. Also, 71% (871) of the same cohort were willing to have children of their own. In addition, 65% (1015) among those surveyed though that infertility had an important social stigma. With respect to gynecological health, 89% (1376) of women surveyed had had at least a gynecologic check-up at the time of answering the survey. However, up to 78% (921) of this cohort had never consulted their gynecologist regarding female fertility. Women surveyed were asked to predict the age at which conceiving a child both naturally and via assisted reproductive techniques started to become difficult. Respondents predicted that age to be 36.74 (IC95% [36.52, 36.96]) years and 39.79 (IC95% [39.58, 40.01]) years, respectively. Plus, 86% (1328) of women surveyed were in favor of elective fertility preservation and up to 72% (1127) thought that the Spanish State should either cover or aid economically this process. Finally, up to 72% (1115) of them thought they lacked important information to take their reproductive choices adequately. Limitations, reasons for caution: Participants in the survey were exclusively contacted virtually. Even with the number of responses obtained and due to the descriptive nature of this study, it might not be representative of Spanish female society regarding the topics addressed. Also, the results here presented might not be extrapolable to other populations. Wider implications of the findings: Considering the data presented in this work, education in fertility should start as soon as possible, ideally in high school. Finally, reproductive autonomy is being able to choose whether to have or not to have children, but the key is to always be able to make that decision. Trial registration number: Not applicable